Marital status, social support, and depressive symptoms among lesbian and heterosexual women. Issue 1 (2nd January 2016) - Kornblith, Erica; Green, Robert-Jay; Casey, Shannon; Tiet, Quyen
ABSTRACT: The current study investigated social support and relationship status (single, dating-but-not-cohabiting, cohabiting, domestic partnership/civil union, married) as predictors of depressive symptoms among lesbian and heterosexual women. The study aimed to determine whether the documented higher rates of depressive symptoms among lesbians compared to heterosexual women could be accounted for by lesbians' reduced access to, or in many cases exclusion from, legalized relationship statuses. The effect of social support from family and social support from friends on depressive symptoms also was examined. Contrary to expectations, results indicated no difference in levels of depressive symptoms among lesbian compared to heterosexual women in this sample. However, regardless of sexual orientation, married women had lower levels of depressive symptoms than unmarried women. Thus, marriage seems to be associated with less depression in lesbian and heterosexual women alike. The interaction of social support and relationship status added to the prediction of depressive symptoms over and above the predictive power of either variable alone, although this effect was small and should be interpreted with caution.